P179 Does Day-case Thoracoscopy Reduce The Number Of Hospital Bed Days For Patients Under Investigation For Unilateral Pleural Effusion?. (10th November 2014) - Fallon, J; Pepperell, J
Abstract : Introduction and objectives: Medical thoracoscopy is the investigation of choice for diagnosis of exudative pleural effusions where pleural cytology is negative and malignancy is suspected. Over the past 18 months, our centre has offered day-case thoracoscopy to suitable patients, with the aim of reducing elective admissions and overall hospital bed days for patients undergoing this procedure. A review of practice has been performed to evaluate whether day-case thoracoscopy is effective in reducing bed days in this cohort of patients. Methods: Data was retrospectively collected from patients attending our centre for medical thoracoscopy over a 12 month period (Feb 2013 – Feb 2014). Information on the number of bed days required, readmission rates and repeat procedures was reviewed for those attending for day-case thoracoscopy and compared with those electively admitted for overnight stay +/- talc pleurodesis. Results: Of 53 patients undergoing medical thoracoscopy at our centre, 31 patients were electively admitted for thoracoscopy, with an average stay of 3.8 bed days. 23 (74%) of this group underwent talc pleurodesis during their initial admission. 13 (42%) patients required readmission within 6 months, extending their total length of stay in this period to 7.3 bed days. 11 (35%) of these patients required further pleural procedure (s) within 6 months of initial thoracoscopy. 22 patients underwent day-case thoracoscopy (initial stay of 0 bed days). 9 (41%) of these patients required re-admission within 6 months, with an average total length of stay of 3.8 bed days. 11 (50%) of these patients went on to require further pleural procedure (s). For the 22 patients attending for day-case thoracoscopy, the number of bed days saved (number of patients x average length of elective admission) was 83.6 bed days. Conclusions: Day-case thoracoscopy reduces the number of hospital bed days in patients under investigation for unilateral pleural effusion and does not lead to increased rates of re-admission for this cohort of patients. Those undergoing day-case thoracoscopy are more likely to require a further pleural procedure, as talc pleurodesis is not performed in this group.